2006
DOI: 10.3390/ijerph2006030002
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin 1-Βeta Cytoprotective Role in AML 12 Mouse Hepatocytes Exposed to Pentachlorophenol

Abstract: Neuregulins are a family of growth factor domain proteins that are structurally related to the epidermal growth factor. Accumulating evidence has shown that neuregulins have cyto- and neuroprotective properties in various cell types. In particular, the neuregulin-1 βeta (NRG1-β) isoform is well documented for its anti-inflammatory properties in rat brain after acute stroke episodes. Pentachlorophenol (PCP) is an organochlorine compound that has been widely used as a biocide in several industrial, agricultural,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…The decrease of MMP caused the release of pro‐apoptotic proteins from the mitochondria leading to caspases activation, and the caspase‐3 as a key executor of apoptosis was activated by many exogenous toxicants. Our study showed that 2,4‐DCP exposure elevated the activity of caspase‐3 in a time‐dependent manner, which is consistent with the results on human lymphocytes exposed to 2,4,5‐trichlorophenol (Michalowicz and Sicinska, ) and on mouse hepatocytes treated by pentachlorophenol (Dorsey et al, ), indicating that the activation of caspase‐3 is also a critical molecular event in 2,4‐DCP‐induced apoptosis. Based on these findings, we proposed that 2,4‐DCP could collapse MMP, activate caspase‐3, and ultimately lead to apoptosis in vitro .…”
Section: Discussionsupporting
confidence: 91%
“…The decrease of MMP caused the release of pro‐apoptotic proteins from the mitochondria leading to caspases activation, and the caspase‐3 as a key executor of apoptosis was activated by many exogenous toxicants. Our study showed that 2,4‐DCP exposure elevated the activity of caspase‐3 in a time‐dependent manner, which is consistent with the results on human lymphocytes exposed to 2,4,5‐trichlorophenol (Michalowicz and Sicinska, ) and on mouse hepatocytes treated by pentachlorophenol (Dorsey et al, ), indicating that the activation of caspase‐3 is also a critical molecular event in 2,4‐DCP‐induced apoptosis. Based on these findings, we proposed that 2,4‐DCP could collapse MMP, activate caspase‐3, and ultimately lead to apoptosis in vitro .…”
Section: Discussionsupporting
confidence: 91%
“…50,51 Induction of CHOP by 2,4,6-TCP led us to ask whether 2,4,6-TCP could induce apoptosis. Previous studies have demonstrated that caspase 3 activation was involved in 2,4,5-trichlorophenol and pentachlorophenol-induced apoptosis in human lymphocytes 33 and mouse hepatocytes, 52 respectively. These findings revealed that caspase 3 is a critical player in CPs-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have shown that oxidative metabolites of PCP are responsible for some of its toxic effects in rodents (Dorsey et al, 2006; Umemura et al, 2006; 2003; Wang et al, 2001). Additionally, PCP has effects similar to butyltin (BT) compounds on NK lytic function and ATP levels (Whalen et al 1999; Dudimah et al 2007a,b) and glutathione and other sulfhydryl containing compounds have been shown to reverse the negative effects of BT compounds on ATP (Cain et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…This data will allow us to determine if PCP is able to interfere with ATP production in NK cells and whether any interference is associated with loss of NK lytic function. Additionally, we examined whether the antioxidants, vitamin E or reduced glutathione, were able to reverse the negative effects of PCP on lytic function and/or ATP levels, as there has been evidence in rodents (Dorsey et al, 2006; Umemura et al, 2006; 2003) and in human hepatoma cell lines (Wang et al, 2001) and human liver cell microsomes (Juhl et al, 1985) that PCP oxidative metabolism is important in its toxic effects in those systems.…”
Section: Introductionmentioning
confidence: 99%